Preliminary Developing PBL-ESDG Learning Tools on Global Warming Topics: Needed to Train Earth Science Literacy and Student Creativity - Desi Wulandari; Shobrina Nurul Mufida; Saniyatul Hikmah (Pendidikan Fisika Universitas Nurul Huda, 2024)
This research aims to analyze the preliminary development process of Problem-Based Learning (PBL) learning tools integrated with Education Sustainable Development Goals (ESDG) on the topic of global warming which aims to train students' earth science literacy and creativity. 3D research design (define, design, develop) is used as a type of initial development research which is an adaptation of 4D design. This research used a validation sheet instrument with assessment indicators in the form of content assessment criteria, presentation criteria, and language criteria. The results of the assessment by 3 experts (2 experts in physics learning instrument development and 1 high school physics learning instructor expert) were analyzed using the percentage of agreement. The research results showed that the entire learning tool was declared valid for each construct, content, and presentation criteria with several improvements. At the development stage, there are improvements to input and suggestions from validators so that the learning tools used are better. Thus, this learning tool can be used for learning to train creativity and earth science literacy for high school students. The recommendation for further research is that this tool can be used as a reference in developing learning tools and implemented in learning on the topic of global warming for high school students level